Recent Advances in Data Logging for Intertidal Ecology - Judge, Richard; Choi, Francis; Helmuth, Brian (Frontiers in Ecology and Evolution, 2018)
Temperature is among the most ubiquitous determinants of organism growth, survival, and reproduction. Accurate recordings and predictions of how the temperatures of plants and animals vary in time and space are therefore critical to forecasting the likely impacts of global climate change. Intertidal zones have long served as a model ecosystem for examining the role of environmental stress on patterns of species distributions, and are emerging as models for understanding the ecological impacts of climate change. Intertidal environments are among the most physically demanding habitats on the planet, and excursions in body temperature of ectotherms can exceed 25°C over the course of a few hours. It is now well-known that the body temperatures of intertidal organisms can deviate significantly from the temperature of the surrounding air and substrate due to the influence of solar radiation, and that their size, color, morphology, and material properties markedly influence their temperatures. While many intertidal organisms are slow moving or almost entirely sessile, for others, behavior can play a significant role in driving vulnerability to temperature extremes. We explore datalogging methods used in intertidal zones and discuss the advantages and drawbacks of each. We show how measurements made in situ reveal patterns of thermal stress that otherwise would be undetectable using more remotely-sensed data. Additionally, we explore the idea that the relevant “grain size” of the physical environment, and thus the spatial scale that must be measured, is a function of (1) the size of the organism relative to local refugia; (2) an organism's ability to sense and to some degree predict near-term environmental conditions; and (3) an animal's movement speed and directionality toward refugia. Similarly, relevant temporal scales depend on the size, behavior, and physiological response of the organism. While miniaturization of dataloggers has significantly improved, several significant limitations still exist, many of which relate to difficulties in recording behavioral responses to changing environmental conditions. We discuss recent innovations in monitoring and modeling intertidal temperatures, and the important role that they have played in bridging ecological and physiological studies of ongoing impacts of climate change.